IMPLEMENTASI NILAI-NILAI ASWAJA DALAM PEMBELAJARAN TEMATIK KELAS 1 MI HIDAYATUL MUBTADI’IN TASIKMADU KECAMATAN LOWOKWARU KOTA MALANG - Dinda Ayu Firdayanti; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
About 90% of Muslims are listed in Islamic books Beliefs, Practices, and Cultures in a world of diverse Sunnis, and the largest Muslim Firqoh is Ahlus Sunnah Waljama'ah, so that educational institutions under the auspices of Ahlussunnah Wal Jamaah become one of the strongest bridges to educate students to understand students' understanding fill in the practice in accordance with the sunnah of the prophet, one of which is MI Hidayatul Mubtadi'in Tasikmadu. MI Hidayatul Mubtadi’in Tasikmadu is an educational institution under the auspices of LP Ma'arif and under the auspices of the Hidayatul Mubtadi'in Islamic Education Foundation which is Ahlussunnah Waljama’ah. The purpose of this study is to analyze and describe the planning, implementation, and evaluation of the application of Aswaja values in the thematic learning of MI Hidayatul Mubtadi’in Tasikmadu, Lowokwaru District, Malang. The researcher collected data through observation, interviews, and documentation. Enter data analysis techniques through data reduction, data display, and conclusions or verification. From the results of this study indicate that the application of Aswaja values in class 1 MI Hidayatul Mubtadi'in Tasikmadu is carried out in the development of activities that perfect Aswaja values, starting from the tawasuf and I'tidal attitudes, tasamuh attitudes, tawazun attitudes, and amr attitudes bi.al-ma'ruf wa.nahy'an al-munkar. Keywords: Implementation of aswaja values, thematic learning